(untitled) (Journal of Computational Mathematics, 2018)
The classical eigenvalue problem of the second-order elliptic operator is approximated with bi-quadratic finite element in this paper. We construct a new superconvergent function recovery operator, from which the O(h^8|h|^2) ultraconvergence of eigenvalue approximation is obtained. Numerical experiments verify the theoretical results.